First report of the rare RhCE‐depleted D‐‐phenotype in sixteen people of Iranian origin. Issue 3 (19th February 2019) - Shahverdi, Ehsan; Moghaddam, Mostafa; Abolghasemi, Hassan
Abstract : Background and Objectives: In transfusion medicine, it may be a challenge to acquire compatible blood for patients who have clinically important alloantibodies to high‐prevalence antigens. The aim of this study was to study prevalence of rare D‐‐ phenotype in samples from patients and their relatives referred to the Immunohematology reference laboratory of the Iranian Blood Transfusion Organization and the detection and identification of the phenotype and associated antibodies, particularly in an antenatal setting. This is the first report of the cases evaluated by the IBTO and family studies of the D‐‐ proposita in Iran and possibly the first attempted comprehensive study in the current transfusion‐related literatures. Materials and Methods: This retrospective cross‐sectional study was carried out on 6720 pregnant women and individuals with difficult positive pretransfusion testing referred for ABO/Rh(D) typing and antibody screening during a period of 8 years from 2008 to December 2016 in the Immunohematology Reference Laboratory of the Iranian Blood Transfusion Organization, Tehran, Iran. Results: During 2008 to December 2016, 16 persons from ten families were detected to have rare D‐‐ phenotype. Anti‐Rh17 and anti‐c were identified in plasma of the 11 persons, including 10 females with a history of multiple unsuccessful pregnancy and the total number of 24 abortions and one male with history of blood transfusion vs. 5 individuals, including an unmarried single woman, 1 person with a history of first‐time pregnancy and 3 persons with a history of multiple pregnancy, who showed no alloimmunization. Based on these collective findings, we interpreted these results as being confirmed as D‐‐ phenotype (0.23%). Conclusion: Irrespective of Rh (D) group a serological antibody screening test is recommended to be required in a National prenatal testing guideline.